Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Pereira-Junior, Sérgio A.G. [UNESP]; Torrecilhas, Juliana A. [UNESP]; Costa, Rayanne V. [UNESP]; Castro Filho, Edivilson S. [UNESP]; Arruda, Maria Carolina G. [UNESP]; Bertoco, João Pedro A. [UNESP]; Feliciano, Andresa L. [UNESP]; Rodrigues, Julia L. [UNESP]; Galati, Rosemary L.; dos Santos, Angélica C.; Chiaratti, Marcos R.; Nociti, Ricardo P.; et al. (Elsevier, 2025)
This study sought to assess the impact of substituting cracked corn grain with soybean molasses (SM) on ruminal degradation patterns in sheep (Exp 1), as well as the performance and meat quality of feedlot-finished male lambs (Exp 2). In Exp 1, nine rumen-cannulated crossbred (Santa Inês × Dorper) male sheep (18 months old; 73.3 ± 2.5 kg BW) were assigned to a triple 3 × 3 Latin square design to assess rumen parameters (pH, ammonia N and SCFA) and in situ degradability of diets containing different levels of SM: CON (0 g kg⁻¹ SM) SM15 (150 g kg⁻¹ SM) and SM30 (300 g kg⁻¹ SM), with a roughage concentrate ratio of 40:60. In Exp 2, twenty male lambs (Santa Inês × Dorper, 98 days old; 21.13 ± 0.92 kg BW) were assigned to randomized block design with two experimental diets: CON (0 g kg⁻¹ SM) and SM20 (200 g kg⁻¹ SM), consisting of 16 % roughage and 84 % concentrate. The animals were evaluated for carcass traits, meat quality (physical and chemical analysis), and muscle transcriptome profile. The inclusion of SM in the diet decreased (P < 0.01) ruminal ammonia concentration and increased (P < 0.01) ruminal pH, while enhancing DM and CP solubility (P < 0.01). No differences were observed in performance, carcass, or meat parameters, but elevated expression was observed in the transcripts involved in fructose metabolism (GO-0006000; P = 4.56 × 10−4) and insulin signaling pathway (hsa04910; P = 0.003), supported by higher triglycerides in blood plasma (P = 0.04) and subcutaneous adipocyte diameter (P = 0.01). Replacing corn with SM in sheep's diets improved the rumen environment and modulated muscle energy metabolism, making it a promising feed alternative for small ruminants.
Keywords: By-product; Meat quality; Rumen fermentation; Soybean molasses